2020
DOI: 10.3389/fmicb.2020.01695
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Motility Is Critical for Salmonella enterica Serovar Typhimurium Biofilm Development

Abstract: The food-borne pathogen Salmonella enterica serovar Typhimurium (S. Typhimurium) causes self-limiting gastroenteritis in humans and is not easily eradicated because it often attaches to suitable surfaces to form biofilms that have high resistance to disinfectants and antimicrobials. To develop an alternative strategy for the treatment of biofilms, it is necessary to further explore the effects of flagellar motility on the development process of Salmonella biofilms. Here, we constructed flagella mutants (flgE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…The relationship between motility and biofilm formation is complex. Although it is widely understood that motility is crucial for initial adhesion [55, 56], there is also an inverse relationship between motility and expression of matrix components; when biofilm matrix production is induced, motility is repressed in a motile-to-sessile lifestyle transition [66, 70, 71]. We found that insertional inactivation of negative motility regulators lrhA and hdfR improved biofilm fitness according to the TraDIS- Xpress data.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The relationship between motility and biofilm formation is complex. Although it is widely understood that motility is crucial for initial adhesion [55, 56], there is also an inverse relationship between motility and expression of matrix components; when biofilm matrix production is induced, motility is repressed in a motile-to-sessile lifestyle transition [66, 70, 71]. We found that insertional inactivation of negative motility regulators lrhA and hdfR improved biofilm fitness according to the TraDIS- Xpress data.…”
Section: Discussionmentioning
confidence: 80%
“…No mutants in flgD and fliE , encoding flagellar filament proteins, were identified at 24 and 48 h, respectively. It has previously been shown that motility is important for initial biofilm formation [55, 56], but this may not relate to biomass formation where no differences were seen for Δ flhD , Δ flhC , Δ fliE and Δ flgD mutants.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between motility and biofilm formation is complex. Although it is widely understood that motility is crucial for biofilm formation 52,53 , it is also true that motility and curli production have an inverse relationship, where biofilm matrix production is induced and motility is repressed for a motile-to-sessile lifestyle transition 67,77,80 . We found that although insertional inactivation of negative motility regulators lrhA and hdfR improved biofilm fitness according to the TraDIS- Xpress data, a Δ hdfR deletion mutant had reduced biofilm biomass, and deletion of either lrhA or hdfR impaired cell aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between motility and biofilm formation is complex. Although it is widely understood that motility is crucial for biofilm formation 47,48 , it is also true that motility and curli production have an inverse relationship, where csgD directly represses fliE 69 and induces c-di-GMP synthesis through adrA, which reduces motility through ycgR [70][71][72] . This is often referred to as a lifestyle 'switch', where biofilm matrix production represses motility for a motile-to-sessile lifestyle transition 73 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation